2019
DOI: 10.1002/joc.6044
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation modulates the spatial variability of temperature in the Atlantic–Arctic region

Abstract: The Arctic region has experienced significant warming during the past two decades with major implications on the cryosphere. The causes of Arctic amplification are still an open question within the scientific community, attracting recent interest. The goal of this study is to quantify the contribution of atmospheric circulation on temperature variability in the Atlantic–Arctic region at decadal to intra‐annual timescales from 1951 to 2014. Daily 20th Century reanalyses geopotential height anomalies at 500 hPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…However, as we will find below, the varied PNA + can lead to a strong typical WWCE dipole under certain SST conditions. To understand what types of PNA + patterns lead to a strong North American WWCE dipole, it is useful to use a k-means clustering method as widely used in previous studies (e. g., Michelangeli et al, 1995;Champagne et al 2019) and C6). It is found that C3 resembling a zonal wave train structure with an anticyclonic (cyclonic) anomaly in the west (east) part of the North America corresponds to a typical WWCE dipole (Fig.…”
Section: B) Composite Results Of Pna + Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as we will find below, the varied PNA + can lead to a strong typical WWCE dipole under certain SST conditions. To understand what types of PNA + patterns lead to a strong North American WWCE dipole, it is useful to use a k-means clustering method as widely used in previous studies (e. g., Michelangeli et al, 1995;Champagne et al 2019) and C6). It is found that C3 resembling a zonal wave train structure with an anticyclonic (cyclonic) anomaly in the west (east) part of the North America corresponds to a typical WWCE dipole (Fig.…”
Section: B) Composite Results Of Pna + Eventsmentioning
confidence: 99%
“…In this paper, we used the k-means clustering method as used in Michelangeli et al, (1995), Ferranti et al, (2015 and Champagne et al, (2019) to classify the different regimes of sub-seasonal S AT and Z500 anomalies over North America (25°N-70°N, 140°W-60°W) for PNA + events during the 1950-2018. Using such a method can help us to identify what types of PNA + patterns favor the WWCE dipole over North America.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we used the k-means clustering method as used in Michelangeli et al, (1995), Ferranti et al, (2015 and Champagne et al, (2019) to classify the different regimes of SAT and Z500 anomalies over North America (25°N-70°N, 140°W-60°W) for PNA + events during the 1950-2018. Using such a method can help us to identify what types of PNA + patterns favor the WWCE dipole over North America.…”
Section: Methodsmentioning
confidence: 99%
“…Based on regional circulation types, air advection from the southern sector was assessed to explain up to 21 and 25% of the SAT variance in the autumn (SON) and winter (DJF), respectively (Łupikasza and Niedźwiedź, 2019). Similar percentages of SAT variance in winter over the Atlantic Arctic (22–27%) were explained by weather regimes in the period 1951–2014 (Champagne et al ., 2019). The meridional circulation, specifically the southern transport of warm and moist air into the Arctic, leads to more efficient absorption of long‐wave radiation, not only at the surface, but also at the higher levels of troposphere (Graversen et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These facts motivated us to check the impact of regional atmospheric circulation on Svalbard SAT. Our research area was selected based on existing studies that imply the crucial role of the atmospheric circulation over the Barents Sea (Bengtsson et al ., 2004; Polyakov et al ., 2010; Chen et al ., 2013; Suo et al ., 2013; Beitsch et al ., 2014; Johannessen et al ., 2016; Walsh et al ., 2017; Wang et al ., 2019) and the Greenland Sea (Ogi et al ., 2016; Walsh et al ., 2017; Champagne et al ., 2019) on the variability and change in the SAT in the Atlantic‐Arctic. This study, which is based on station data, is important because most of the knowledge on historical Arctic warming comes from model projections (Tokinaga et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%